Consumer Behavior and Perceive to Buy from Ready-to-Eat Meals Meat-Based Products: a Case Study of Rendang Tastes Processed Meats in Indonesia - Permana M.A.; Aprianingsih A.; Fadlullah H.M. (Journal of Social Research, 2023)
Consumer behavior plays a pivotal role in the success of marketing strategies as it determines how consumers perceive and interact with products in the market. This study examines consumer behavior and perceptions in buying rendang-flavored processed meat as ready-to-eat (RTE) products in Indonesia. The research focuses on identifying the factors influencing consumers to purchase rendang taste processed meats, understanding their perceptions of the product, and assessing the impact of marketing strategies on their purchasing decisions. Data were collected using a survey with 211 final respondents, a quantitative method of Partial Least Squares - Structural Equation Modelling (PLS-SEM) was used to analyze the data. The findings of this study offer valuable insights into consumer behavior and perception towards rendang-flavored processed meats in Indonesia. The research is anticipated to have intellectual merit by exploring consumer behavior towards RTE products specific to Indonesian consumers. The practical implications of this study can aid companies in developing effective marketing strategies that capitalize on consumer preferences and ultimately increase sales and profitability.